Potential for Respiratory Epithelium Regeneration from Induced Pluripotent Stem Cells. (January 2013) - Otsuki, Koshi; Imaizumi, Mitsuyoshi; Nomoto, Yukio; Wada, Ikuo; Miyake, Masao; Sugino, Takashi; Omori, Koichi
Objectives: In cases of laryngeal inflammatory lesions and tracheal invasion of a malignant tumor, autologous tissue implantation techniques using skin or cartilage are often applied. However, these techniques are both invasive and unstable. The purpose of this study was to evaluate the potential use of induced pluripotent stem (iPS) cells in the regeneration of respiratory epithelium. Methods: We seeded iPS cells on low-attachment plates in serum-free media to generate embryoid bodies (EBs). After a 3-day culture, the EBs were transferred to a gelatin-coated dish supplemented with activin A alone or with basic fibroblast growth factor (induction groups). As a control, EBs were cultured without these growth factors (control group). Cultured tissues from all groups were histologically examined for 2 weeks. Results: In the induction groups, the presence of respiratory epithelium-like tissue was observed with hematoxylin and eosin staining after 14 days of culture. Conclusions: This study demonstrated the potential use of iPS cells in regeneration of the respiratory epithelium.